A Three Sample Test of Some Extensions to the Job Characteristics Model of Work Motivation - Champoux, Joseph E. (Academy of Management Journal, 1980)
Two theoretical extensions to the Hackman and Oldham (1976) job characteristics model of work motivation describe: (1) the relationship between job scope and psychological response as curvilinear, and (2) growth need strength as moderating the curvilinear relationship. Data from three samples supported only the first extension to the model.